Teaching Writing through Process-Genre Method - Santi Ariyanti (Channing : Journal of English Language Education and Literature, 2019)
The main problem of this study was "Is it effective to teach writing through the process-genre method to the tenth-grade students of Islamic Senior High School NU Yosowinangun?". The objective of this study is to find out whether the process-genre method was effective to teach writing to the tenth-grade students of Islamic Senior High School NU Yosowinangun, writing ability of descriptive text. This research used a quantitative research method using the pre-experimental method. The population of the study was all the tenth-grade students of Islamic Senior High School NU Yosowinangun in the academic 2019/2020, with 106 students. The sample was 20 students taken by using one-stage cluster random sampling. The data were analyzed through the matched t-test formula to find out the effectiveness of teaching writing through the process-genre method. The technique for collecting data used a written test twice in the pre-test and post-test. Based on the result of the data analysis, it was found that the highest score in the pre-test was 69 and the lowest score was 41, and the average score was 52.8. While in the post-test, the highest score was 85 and the lowest score was 70, where the average score was 79, it was found that the value of t-obt was 18.7, where the value of t-tab was 1.725, at significance level 0.05 or 95% with a degree of freedom. . It can be concluded that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It indicated that teaching writing through the process-genre method to the tenth-grade students of Islamic Senior High School NU Yosowinangun was effective.